Modalism Revisited: A Defence - Monika Morkūnaitė (Problemos)
Modalism, a philosophical theory positing that modal concepts such as possibly and necessarily are primitive and unanalysable, stands in contrast to possible worlds semantics, which analyses modal notions through a quantificational framework. This article examines the core tenets of modalism, building upon works by Arthur Prior, Kit Fine, and Graeme Forbes. The article then addresses criticisms from figures like David Lewis, who holds that taking modal idioms as primitive does not count as genuine theorising, and Joseph Melia, who argues that modalist language implicitly mimics possible worlds semantics. The article suggests that modalist formalisations draw from natural language instead of making implicit use of possible worlds semantics. It further highlights that modalism provides a more intuitive understanding of modal concepts compared to possible worlds semantics.